THE TRANSPARENCY OF INFORMATION IN TERMS OF CRIME CLEARANCE IN BANGKALAN POLICE RESORT AREA AS A CONTROL FOR POLICE PERFORMANCE BY SOCIETY - Effendi, Tolib (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Transparency of information became one of the legal reform agenda within the theme of strengthtening the rule of law. Without any public transparency of information, particulary in terms of the completion of criminal cases (crime clearance) by the police, then how can the public contribute to monitor the criminal justice system. Therefore, it needs to be re-examined regarding the transparency of information about the completion of the criminal case as one of the control performance of the police by the public. This research is a descriptive – exploratory elaborated on the level of transparency of information about the crime clearance of the case in the Police Bangkalan as one of the control performance of the police by the public. The transparency of information about the number of cases solved by the Police Bangkalan certaintly can support public trust in the performance conducted by the police. This study started from the idea that one model of control that occur in Indonesia within the framework of the criminal justice system is community involvement in monitoring/ control of law enforcement.Keyword: Transparency, Control, Police, Public.